2022
DOI: 10.1111/jcpe.13721
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for tooth loss and progression of periodontitis in patients undergoing periodontal maintenance therapy

Abstract: Aim The aim of this study was to investigate patient‐ and tooth‐level factors that may predict tooth loss and periodontitis progression in patients who have undergone at least 5 years of periodontal maintenance. Materials and Methods In this retrospective cohort study, 135 patients were examined after active periodontal therapy (APT) and periodontal maintenance for 5.09–8.65 years (mean 6.16 ± 0.74 years). Regression models were applied to identify risk factors associated with tooth loss and disease progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…‘Controlled periodontitis’ was the most frequently achieved endpoint (52.42%) among studies following conventional APT. At the subject level, it has an RR of 2.78 ( p = .0068) of tooth loss during SPC when not achieved, which is similar to the findings reported elsewhere (Siow et al, 2022). Unlike other subject‐level endpoints, this endpoint considers multiple residual sites, which is relevant, as subject‐ and tooth‐level factors can affect the treatment response, particularly in relation to specific tooth types (Tomasi et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…‘Controlled periodontitis’ was the most frequently achieved endpoint (52.42%) among studies following conventional APT. At the subject level, it has an RR of 2.78 ( p = .0068) of tooth loss during SPC when not achieved, which is similar to the findings reported elsewhere (Siow et al, 2022). Unlike other subject‐level endpoints, this endpoint considers multiple residual sites, which is relevant, as subject‐ and tooth‐level factors can affect the treatment response, particularly in relation to specific tooth types (Tomasi et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in agreement with previous studies, suggesting that TL is a consequence of periodontal disease that is occasionally observed and must be prevented. 6,26 RPc are commonly observed after APT. [27][28][29] In the present study, about 89% of the individuals had at least one site with RPc ≥ 5 mm and 70% with RPc ≥ 6 mm.…”
Section: (A) Variablesmentioning
confidence: 99%
“…Numerous patient-related (age, sex, smoking, diabetes mellitus, severity of the disease, and compliance with SPT) and tooth-related factors (tooth type, tooth location, probing depth [PD], bleeding on probing [BOP], presence of furcation involvement, mobility, and bone loss) have been suggested to increase the risk of TL or TLP during SPT, including the presence of residual pockets (RPc). 1,[4][5][6][7] According to the 2017 World Workshop Classification (WWC), periodontal health in a successfully treated periodontitis patient can be described as PD ≤4 mm at all sites or no PD ≥4 mm with BOP. 8 The European Federation of Periodontology has established the absence of RPc >4 mm with BOP or no deep pockets ≥6 mm as the endpoint of periodontal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…4 In severe cases, it can directly lead to tooth loosening or loss. 5 Several studies have also demonstrated an association between periodontitis and systemic diseases, such as Alzheimer's disease, 6,7 cardiovascular disease, 8,9 and diabetes. 10,11 The optimal treatment period for periodontitis focuses on prevention and early mild symptoms, controlling inflammation with medication, regulating the immune response, and reducing tissue fester.…”
Section: Introductionmentioning
confidence: 99%
“…4 In severe cases, it can directly lead to tooth loosening or loss. 5 Several studies have also demonstrated an association between periodontitis and systemic diseases, such as Alzheimer's disease, 6,7 cardiovascular disease, 8,9 and diabetes. 10,11…”
Section: Introductionmentioning
confidence: 99%